Analisis Romantisme dan Makna Hiperbola Pada Puisi “Syair Rindu” Karya Marah Roesli - Irfanda Siti Amaliyafitri (Concept: Journal of Social Humanities and Education, 2022)
This article discusses the hidden meaning of the poem by Marah Roesli. This discussion aims to better understand the reader about the content of the poem. The poem "Syair Rindu" is one of the poems that has such a deep meaning if it is interpreted because it contains the meaning of romanticism. Marah Roesli is an Indonesian writer from the Balai Pustaka group, or the literary period that emerged during the Dutch colonial period in the 1920s to 1930s. This article also discusses the meaning of hyperbole in the poem "Syair Rindu".